2015
DOI: 10.1088/0268-1242/30/10/105009
|View full text |Cite
|
Sign up to set email alerts
|

Negative bias temperature instability in p-channel power VDMOSFETs: recoverable versus permanent degradation

Abstract: In this study, which is aimed at assessing a possible relationship between the recoverable and permanent components of negative bias temperature instability (NBTI) degradation, we investigate NBTI in commercial IRF9520 p-channel VDMOSFETs (vertical double diffused MOSFETs) stressed under particular pulsed bias conditions by varying the pulse on-time while keeping the off-time constant and vice versa. The stress-induced threshold voltage shifts are found to be practically independent of duty cycle when the puls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…2, NBT stress caused negative threshold voltage shifts ΔV T of 0.28-0.3 V in virgin devices. The observed results can be explained by means of the standard reaction-diffusion (RD) model, which includes reactions involving holes at the Si − SiO 2 interface and in the oxide near interface, accompanied by the release of hydrogen species and their transport through the oxide [25], [26], [31]- [33]. Briefly, a high electric field at elevated temperature in the presence of holes may cause dissociation of weak Si-H bonds at the interface…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2, NBT stress caused negative threshold voltage shifts ΔV T of 0.28-0.3 V in virgin devices. The observed results can be explained by means of the standard reaction-diffusion (RD) model, which includes reactions involving holes at the Si − SiO 2 interface and in the oxide near interface, accompanied by the release of hydrogen species and their transport through the oxide [25], [26], [31]- [33]. Briefly, a high electric field at elevated temperature in the presence of holes may cause dissociation of weak Si-H bonds at the interface…”
Section: Resultsmentioning
confidence: 99%
“…However, in practice, p-channel power VDMOSFETs are more likely to operate in the dynamic regime than in the static one. Keeping in mind that NBTI effects in dynamically stressed devices are less pronounced [23], [26], it can be concluded that in practical operation, p-channel VDMOSFETs will be less degraded. Under the assumption that high temperature at least does not increase their radiationinduced threshold voltage shift (a decrease of positive oxide charge due to annealing and eventual increase in the density of switching traps would be compensated in p-channel devices), their radiation tolerance level (for defined failure criteria) will be increased.…”
Section: Resultsmentioning
confidence: 99%
“…Experiments were done at two different temperatures (150 °C and 175 °C) and values of threshold voltage shifts are obtained. Our ear-lier experiments included testing devices under many different conditions in terms of both gate voltage and temperature [9][10][11][12][13]. Experimental results are given in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…Despite notable scale down in the device dimensions, ultra-thick gate oxide reliability studies are still of significance because of broad use of MOS technology. Taking this into consideration, our earlier papers were dealing with NBTI in p-channel power vertical double diffused MOS (VDMOS) transistors [6,[8][9][10][11][12][13]. Their reliability has been investigated under various stress conditions, such as irradiation, high electric field, NBTI, NBTI under low magnetic field, and NBTI and irradiation [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…In many of these applications devices may be subjected to stress or harsh environment conditions. Accordingly, investigation of their reliability and related effects is of high importance [1][2][3][4][5][6][7][8][9][10][11].…”
Section: Development Of Advanced Electronic Industry Is Based On Combmentioning
confidence: 99%